二项式反演

\[f(n)=\sum_{i=0}^n{n\choose i}g(i) \iff g(n)=\sum_{i=0}^n(-1)^{(n-i)}{n\choose i} f(i) \]

证明如下:

\[g(n)=\sum_{i=0}^n(-1)^{n-i}{n \choose i} \sum_{j=0}^i {i\choose j}g(j)\\ g(n)=\sum_{i=0}^n \sum_{j=0}^i (-1)^{n-i}{n \choose i} {i\choose j}g(j)\\ g(n)=\sum_{j=0}^n \sum_{i=j}^n (-1)^{n-i}{n \choose i} {i\choose j}g(j)\\ \]

\[{i \choose j}{j \choose k}=\frac{i!j!}{j!(i-j)!k!(j-k)!}\\ =\frac{i!(i-k)!}{(i-j)!(i-k)!k!(j-k)!}\\ =\frac{i!}{k!(i-k)!}\frac{(i-k)!}{(i-j)!(j-k)!}\\ =\frac{i!}{k!(i-k)!}\frac{(i-k)!}{(j-k)!((i-k)-(j-k))!}\\ ={i \choose k}{i-k \choose j-k} \]

\[g(n)=\sum_{j=0}^n \sum_{i=j}^n (-1)^{n-i}{n \choose j} {n-j\choose i-j}g(j)\\ g(n)=\sum_{j=0}^n \sum_{i=0}^{n-j} (-1)^{n-i-j}{n-j\choose i} {n \choose j} g(j)\\ \]

\[\sum_{i=0}^{n-j} (-1)^{n-i-j}{n-j\choose i}1^{i}\\ (1-1)^{n-j} \]

\[g(n)=\sum_{j=0}^n (1-1)^{n-j}{n \choose j} g(j)\\ g(n)=g(n)\\ \]

posted @ 2019-12-05 09:40  DQY_dqy  阅读(107)  评论(0编辑  收藏  举报